The Role of Leadership and Power in Performance Assessment to Improve Human Resources in School Organizations: A Systematic Literature Review - Hema Malini (Jurnal Sinar Edukasi, 2021)
The purpose of this study is to explore and analyze how leadership and power contribute to performance appraisal and how they impact HR development in schools. The method employed is a Systematic Literature Review (SLR) of publications from 2020 to 2024, collecting and analyzing articles relevant to the specified keywords. The findings indicate that effective leadership, supported by the appropriate exercise of power, has a significant impact on HR performance in schools. Leaders who adopt transformational and participatory leadership styles tend to be more successful in fostering teacher motivation and engagement, which in turn contributes to improved educational quality. Furthermore, transparent and equitable performance appraisals strengthen trust and commitment among organizational members. The review also identifies several challenges in implementing performance appraisals, including resistance to change and insufficient managerial support. Accordingly, the study recommends targeted training and development for school leaders to enhance leadership competencies and deepen understanding of the strategic role of power in educational contexts. Overall, this study offers important insights into the interrelationship among leadership, power, and performance appraisal in improving HR within school organizations, and is expected to serve as a reference for educational leaders and policymakers in formulating effective HR development strategies.